The Movement of Wheat-Growing: A Study of a Leading State - Thompson, C. W. (Quarterly Journal of Economics, 1904)
Journal Article The Movement of Wheat-growing: A Study of a Leading State Get access C. W. Thompson C. W. Thompson University of South Dakota Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 18, Issue 4, August 1904, Pages 570–584, https://doi.org/10.2307/1882417 Published: 01 August 1904